2013
DOI: 10.1088/1742-5468/2013/09/p09023
|View full text |Cite
|
Sign up to set email alerts
|

A new family of exactly solvable disordered reaction–diffusion systems

Abstract: Using a matrix product method the steady-state of a family of disordered reaction-diffusion systems consisting of different species of interacting classical particles moving on a lattice with periodic boundary conditions is studied. A new generalized quadratic algebra and its matrix representations is introduced. The steady-states of two members of this exactly solvable family of systems are studied in detail.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…, µ) at the nearest neighbors. Thus, the microscopic dynamics considered here is different from previously studied models like TASEP with internal degrees of freedom [64] and multi-species reaction-diffusion processes [65,66]. Notably, the distinction in the microscopic dynamics also makes µ-ASEP-IAF non-ergodic in nature in contrast to the ergodic models [64][65][66].…”
Section: Introductionmentioning
confidence: 72%
“…, µ) at the nearest neighbors. Thus, the microscopic dynamics considered here is different from previously studied models like TASEP with internal degrees of freedom [64] and multi-species reaction-diffusion processes [65,66]. Notably, the distinction in the microscopic dynamics also makes µ-ASEP-IAF non-ergodic in nature in contrast to the ergodic models [64][65][66].…”
Section: Introductionmentioning
confidence: 72%
“…, µ) at the nearest neighbors. Thus, the microscopic dynamics considered here is different from previously studied models like TASEP with internal degrees of freedom [61] and multi-species reaction-diffusion processes [62,63]. Notably, the distinction in the microscopic dynamics also makes µ-ASEP-IAF non-ergodic in nature in contrast to the ergodic models [61][62][63].…”
mentioning
confidence: 72%
“…Thus, the microscopic dynamics considered here is different from previously studied models like TASEP with internal degrees of freedom [61] and multi-species reaction-diffusion processes [62,63]. Notably, the distinction in the microscopic dynamics also makes µ-ASEP-IAF non-ergodic in nature in contrast to the ergodic models [61][62][63]. We should mention that the non-ergodicity of exactly solvable models is related to undecidability of thermalization in integrable models [64].…”
mentioning
confidence: 72%
“…In [17] the authors have shown that the quadratic algebra (10) has a finitedimensional representation which depends on the number of types of particles. The dimension of the matrix is M if the number of types of the particles is equal to M. Hence for our model with two species of particles the quadratic algebra (10) has a 2-dimensional matrix representation given by…”
Section: The Spatial Correlationsmentioning
confidence: 99%
“…To find the critical exponent defined by q / ðz À z c Þ b , we only need to consider the behavior of the density of the first-class particles as a function of fugacity z at the critical point z c ¼ 1þqÀp p in the thermodynamic limit. According to (17), it can be seen that the density of the first-class particles in the vicinity of z c can be With the correlation function given asymptotically by…”
Section: The Spatial Correlationsmentioning
confidence: 99%